Public Expenditure Impact and Income Distribution Analysis in Malaysia Using a Social Accounting Matrix Framework - Harun, Mukaramah (2010)
Income distribution issues continue to grasp attention in Malaysia as income inequality between ethnic, urban and rural still remains wide and persistent. Distribution trend shows that income inequality has reduced since 1970, but has been rising again since 1999. The objective of this thesis is to analyze the impact of public expenditure on income distribution in Malaysia. Specifically the objectives of the thesis are threefold.First, to examine the initial functional and institutional distribution of income across different institutional agents and sectors. Second, to evaluate the impact of the public expenditure policies in reducing the inter-ethnic and rural-urban disparity. Third, to assess the impact of public expenditure policies in different Malaysia Plan on income distribution among household sector.